2000
DOI: 10.1177/00220345000790061301
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Bone Formation Rates in Aged Ovariectomized Rats Treated with Anti-resorptive Agents Alone and in Combination with Intermittent Parathyroid Hormone

Abstract: Anti-resorptive agents--including estrogen (E), calcitonin (CT), and bisphosphonates--are established in the treatment of osteoporosis. Intermittent administration of parathyroid hormone (PTH) stimulates bone formation and is a possible therapeutic agent for the restoration of bone mass. The purpose was to determine the effects of the anti-resorptive agents alone and in combination with intermittent PTH on bone formation in the mandible and a long bone in the aged ovariectomized (Ovx) rat. Female rats were ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
4
29
0
3
Order By: Relevance
“…Consequently, analysis of our data has indeed shown significant positive PTH effects on BMD/BMC and calcium content of peri-alveolar bone. Thus, these results and those of others (Miller et al, 1997;Hunziker et al, 2000) support a beneficial effect of intermittent PTH administration in osteoporosis patients with periodontal disease, either alone or in combination with anti-resorptive agents. Moreover, an additional PTH benefit is that it might abrogate the risk of developing jaw osteonecrosis associated with bisphosphonates (Hess et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, analysis of our data has indeed shown significant positive PTH effects on BMD/BMC and calcium content of peri-alveolar bone. Thus, these results and those of others (Miller et al, 1997;Hunziker et al, 2000) support a beneficial effect of intermittent PTH administration in osteoporosis patients with periodontal disease, either alone or in combination with anti-resorptive agents. Moreover, an additional PTH benefit is that it might abrogate the risk of developing jaw osteonecrosis associated with bisphosphonates (Hess et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…One previous report showed that PTH stimulated dentin apposition in the thyroparathyroidectomized rat in a dose-dependent manner (Turnbull et al 1983), but another study showed that intermittent PTH treatment had no effect on dentin formation in aged ovariectomized rats . Although intermittent PTH treatment was shown to stimulate mandibular and alveolar crest bone formation in aged ovariectomized rats , the increased mineral apposition rate was much less in mandibles than in long bones (Hunziker et al 2000). Therefore, these findings suggest that the sensitivity of skeletal tissues to PTH may vary according to their embryological origin (Yonaga 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Sustained elevated levels of PTH, such as occur in hyperparathyroidism, can be detrimental to skeletal metabolism; however, when given intermittently, PTH can be extremely anabolic (17). Intermittent administration of PTH increases both cortical and cancellous bone content (15,(18)(19)(20). Hunziker et al have demonstrated that intermittent PTH administration stimulates bone formation in the mandibles of aged ovariectomized rats (15,19).…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent administration of PTH increases both cortical and cancellous bone content (15,(18)(19)(20). Hunziker et al have demonstrated that intermittent PTH administration stimulates bone formation in the mandibles of aged ovariectomized rats (15,19). Hence, it is possible that the response to the local bone-forming stimulus of rhBMP-2 was enhanced by the elevated bone metabolism caused by the daily injection of PTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation